Identification of Clostridium perfringens and Salmonella spp. in Swine Through PCR - Boarini, Livia [UNESP]; Beraldo-Massoli, Mariana Casteleti [UNESP]; Casagrande, Mariana Froner [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Makino, Lilian Cristina [UNESP]; Souza, Andressa de [UNESP]; Lima, Marco Monteiro de [UNESP]; Maldonado, Walter [UNESP]; Schocken-Iturrino, Ruben Pablo [UNESP] (Univ Fed Rio Grande Do Sul, 2015)
Background: The presence Clostridium spp. and Salmonella spp. is the main concern in swine sector, since they interfere in the microbiological quality of meat and can be responsible for several diseases, presenting occurrences such as intestinal infections and enterotoxaemia. It is necessary to improve production and quality of meat and by-products swine ensuring good quality origin of products marketed. Considering these aspects, the objective of the present study was to assess the presence of Clostridium perfringens and Salmonella spp. in pigs destined for consumption, with bacterial counts and identification using PCR technique. Materials, Methods & Results: The collections were made at slaughterhouse and confinement, with bacterial count by the pour-plate technique with Reinforced Clostridial Agar, and the identification by PCR with cpa, cpb, IA, cpe, etx and cpb-2 genes for C. perfringens; and invA and fliC for Salmonella spp. The scores presented average values of 6.04 x 10(4) CFU/mL for confinement, and 1.8 x 104 CFU/mL in the slaughterhouse. The means counts between the confinement and slaughterhouse groups showed significant difference (P < 0.01). The samples taken at the slaughterhouse were from several farms at random, and allowed the appraisal of hygienic conditions, since animals of confinement remained sanitized and the accumulation of feces on floor was avoided. The PCR technique presented positive results for C. perfringens alpha toxin (cpa) in 25% of the confinement samples, and 46.4% in the slaughterhouse. Salmonella spp. was identified in 9.5% of confinement and 21.4% of the slaughterhouse. Discussion: The presence of C. perfringens and Salmonella spp. is directly related to losses in the entire system of creation of pigs, since infected animals are susceptible to severe diseases, or without clinical signs can exhibit apathy and loss of appetite making weight gain difficult and causing deficiency of the immune system. The difference between the averages counts of the confinement and the slaughterhouse may be due to several factors, but environmental conditions and hygienic are the most influence these differences. When the slaughterhouse samples were collected, the contact with swine of the other farm and the stress of transport may allow the excretion of C. perfringens in greater quantity than usual, while the animals of confinement remained in stalls separate and stress-free the whole period. Many researches have been demonstrating that the identification of pathogenic bacteria by PCR has been more sensitive and faster than conventional microbiology. For this work, this technique gave swift and reliable results, since it consisted of amplification of specific genes to the species of C. perfringens and Salmonella spp. and S. Typhimurium. This fact is of great relevance to contribute preventively with the diagnosis and treatment of animals before they can cause damage to the sector. This comparison can be confirmed when observed the correlation coefficient (-0,25) between detection of bacterial and weight of animals confined. These results demonstrate that animals with high count of bacteria were those who had greater difficulties in gaining weight, and consequently were slaughtered below the ideal weight. It could be concluded that C. perfringens and Salmonella spp. are often related directly to negative influence on pig production, mainly in initial confinement hindering the weight gain of the animals, and in the industry sector contaminating the meat and its derivatives. Moreover, the molecular biology methods showed to be quite efficient when compared to the conventional ones, thus, PCR can be considered a useful tool to improve pig production.
Keywords: anaerobic bacteria; swine production; slaughterhouse